Effect of Career Maturity, Organizational Culture, and Job Satisfaction Against the Performance of Lecturers of State Islamic University Sultan Aji Muhammad Idris (UINSI) Samarinda - Lina Revilla Malik; Dwi Nugroho Hidayanto; Hasbi Sjamsir (Educational Studies: Conference Series, 2022)
The purpose of this study was to know (1) whether career maturity has a significant and positive effect on the performance of UINSI Samarinda lecturers, (2) whether organizational culture has a significant and positive effect on the performance of UINSI Samarinda lecturers, (3) whether job satisfaction has a significant and positive effect on the performance of UINSI Samarinda lecturers, (4) whether career maturity, organizational culture, and job satisfaction together have a significant and positive effect on the performance of UINSI Samarinda lecturers. The research population was 211, while the number of samples taken in this study was 122 using the Taro Yamane formula using non-proportionate cluster random sampling. The instrument used is a questionnaire, then analyzed utilizing multiple linear regression. Based on the results of statistical tests and discussions, the researchers concluded that (1) Career maturity has a significant and positive effect on the performance of UINSI Samarinda lecturers. There is an influence of career maturity on the performance of lecturers at the medium category level with the percentage contribution of the X1 variable to Y being 23.23%. (2) Organizational culture has a significant and positive effect on the performance of UINSI Samarinda lecturers. There is a positive and significant influence of organizational culture on the performance of lecturers at the low category level with the percentage contribution of the X2 variable to Y being 11.09%. (3) Job satisfaction has a significant and positive effect on the performance of UINSI Samarinda lecturers. There is a positive and significant effect of job satisfaction on the performance of lecturers in the low-level category with the percentage contribution of the X3 variable to Y being 8.58%. (4) Career maturity, organizational culture, and job satisfaction together have a significant and positive effect on the performance of UINSI Samarinda lecturers. There is a positive and significant effect of career maturity variables (X1), organizational culture (X2), and job satisfaction (X3) together on lecturer performance (Y) at the medium level category with the percentage contribution of variables X1, X2, and X3 to Y is 29.45%.